The Concept of Family Education in Surah Luqman Verses 12–19 - Hidayatullah; Wulan Safitri; Rachmawati Fitriyah; Benny Prasetiya (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
This study aims to analyze the concept of family education contained in Surah Luqman verses 12–19 and to examine its relevance to contemporary educational and psychological theories. This research employs a qualitative approach using a library research method through thematic analysis of the Qur’anic text, classical and contemporary exegetical works, and academic literature related to family education and moral development. Data analysis was conducted using content analysis to identify the pedagogical structure within Luqman’s counsel to his son. The findings reveal that Surah Luqman verses 12–19 contain a systematic and holistic pedagogical framework for family education that can be mapped into five main pillars a spiritual theological foundation through the inculcation of the values of tawḥid and gratitude, relational education emphasizing respect for parents and proportional obedience, the development of moral awareness and personal responsibility, the habituation of religious practices and the strengthening of emotional regulation through prayer, amr maʿrūf nahy munkar, and patience ṣabr, and the cultivation of social ethics, courtesy, and behavioral moderation. These findings indicate that Luqman’s pedagogy aligns with several contemporary educational theories, including positive psychology, attachment theory, moral development theory, self regulation theory, and social learning theory. Therefore, the educational values embedded in Surah Luqman verses 12–19 demonstrate strong relevance in addressing the challenges of contemporary family education and contribute to the development of an integrative and holistic model of character education.